On the asymptotic formulas of solutions to the boundary value problem without initial condition for Schrödinger systems in domain with conical points. (January 2016) - Hung, Nguyen Manh; Lien, Nguyen Thi
Abstract: In this paper, boundary value problems without initial condition for Schrödinger systems in domains with conical points are considered. We establish several results on the asymptotic behavior of solutions near singular points.